2000
DOI: 10.1080/09540120050042972
|View full text |Cite
|
Sign up to set email alerts
|

First injection and current risk factors for HIV among new and long-term injection drug users

Abstract: The purpose of this paper is to estimate HIV seroprevalence and to examine the injection and sexual risk behaviours of a cohort of active new heroin injectors who have initiated injection within the past four years and to compare their risk behaviours with those of long-term heroin injectors who initiated injection prior to January 1, 1985. A stratified network-based sample was used to recruit injection drug users (IDUs) from the streets of Miami-Dade, Florida. New IDUs displayed a significantly lower HIV sero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(8 citation statements)
references
References 0 publications
0
7
1
Order By: Relevance
“…Existing research has documented the numerous social and health consequences associated with long-term heroin use including blood-borne pathogen infections, depression, and high frequency overdoses (Chitwood et al, 2000; Hser, 2007; Rajaratnam, Sivesind, Todman, Roane, & Seewald, 2008; Rosen, Hunsaker, Albert, Cornelius, & Reynolds, 2011; Rosen, Smith, & Reynolds, 2008). Although the public health implications have been consistently documented, the debate concerning the “natural history” or “drug career” of long-term heroin use is ongoing (Best, Ghufran, Day, & Ray, 2008; Genberg et al, 2011; Hser, Hoffman, Grella, & Anglin, 2001; Hser, Longshore, & Anglin, 2007; Weiss et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Existing research has documented the numerous social and health consequences associated with long-term heroin use including blood-borne pathogen infections, depression, and high frequency overdoses (Chitwood et al, 2000; Hser, 2007; Rajaratnam, Sivesind, Todman, Roane, & Seewald, 2008; Rosen, Hunsaker, Albert, Cornelius, & Reynolds, 2011; Rosen, Smith, & Reynolds, 2008). Although the public health implications have been consistently documented, the debate concerning the “natural history” or “drug career” of long-term heroin use is ongoing (Best, Ghufran, Day, & Ray, 2008; Genberg et al, 2011; Hser, Hoffman, Grella, & Anglin, 2001; Hser, Longshore, & Anglin, 2007; Weiss et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This focus reflects the persistent observation that most PWIDs initiate drug injection in their late teens and early twenties. Indeed, observational epidemiological studies have consistently found the mean age of first injection to range from 19 to 22 (Broz et al, 2013; Carneiro et al, 1999; Chitwood et al, 2000; Des Jarlais et al, 1999). Thus, the focus on younger PWID seems appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…Three studies from the 1990s found that new injectors (having initiated injection drug use within the last 6 years) had a mean age of first injection in the range of 25 to 30 (Carneiro et al, 1999; Chitwood et al, 2000; Des Jarlais et al, 1999). Unpublished data from the National Institute for Drug Abuse’s (NIDA) 23-city Cooperative Agreement for AIDS Community-based Outreach/Intervention 1990s (Kral et al, 1998; Stephens et al, 2000), indicate that approximately 16% of PWIDs initiated drug injection at age 30 or later in this multi-site US study.…”
Section: Introductionmentioning
confidence: 99%
“…Of those infected with HIV, approximately 14% are IDUs and 2% are MSM who are also IDUs. Given an HIV seroprevalence rate of 19% (Chitwood et al, 2000) there are approximately 23,700 IDUs in Miami, i.e., approximately 1.4% of the total Miami metropolitan population aged 18 years or older. Gender differences are apparent in Miami.…”
Section: Introductionmentioning
confidence: 99%